Effect of steam-drying treatment on moisture content, drying rate, color, and drying defects in juvenile wood of Tectona grandis from fast-growth plantations. Issue 15 (18th November 2017) - Moya, Róger; Berrocal, Alexander; Rodriguez-Solis, María; Muñoz, Freddy
ABSTRACT: Tectona grandis is the second most important species for reforestation in Costa Rica, and any improvement in its industrialization process is important, especially the drying process. Lumber obtained from a plantation of 12-year-old T. grandis trees was used to evaluate three drying schedules that include integrated steaming processes to determine the combined effect of the steam-drying system on the dried lumber. The variations in the moisture content (MC) and drying rate (DR) with drying time (DT) both before and after the steaming process were modeled mathematically for boards that have a flat and quarter grain pattern. For both types of boards that were dried with and without steaming, a relationship between MC and DT was observed. There was inflexion at 40%, and two mathematical models were computed. Additionally, the relationship between DR and DT for boards with flat and quarter grain patterns was not affected by the steaming process, and an inflection point was observed at 30 h (40% MC for the lumber). Moderate changes were observed in the CIELAB color system and dried lumber became darker. The steaming process, which was integrated in the drying schedule for boards with the flat and quarter grain pattern, decreased the incidence or magnitude of drying defects depending on the grain pattern and drying schedule used.